The Effect of Price and Brand Image of Smartphone Toward Purchasing Decision of Muslim Consumers (Case Study Student University of Darussalam Gontor Campus 6 Magelang) - Imam Haryadi; Fadly Arif (Islamic Economics Journal, 2018)
In a competitive businesses situation that increasingly going forward at this time, companies need to utilize their resources optimally that can aff ect consumers’ perception on purchasing, as an example in adjusting the price and also improving their the brand image. In Islamic law, Excessive consumption is called by the term israf or tabzir (wasting resourches without any good use). As a consumer and student of Islamic economics, more throughly before buying a product is very important, especially for students UNIDA Magelang. The purpose of this research is to fi nd out the eff ect of price and brand image of Smartphone toward purchasing decision of muslim consumers. This research is quantitative research, the data used in this research is primary data obtained from the questionnaires that distributed to the respondents, with 67 persons as a sample. The data analysis techniques by using validity test, reliability test, multiple regression and classical assumption test. The result of this research show that the price and brand image of Smartphone aff ect purchasing decision of muslim consumers, with value of (t) count 2.006 for price, and 5.900 for brand image. Based on these values, it is concluded that brand image has more signifi cantly eff ect toward purchasing decision of muslim consumers than the price. And the eff ect from price and brand image of Smartphone toward purchasing decision of muslim consumers is 52,2%, and 47,8% is influanced by other factors.